New agents and regimens for diffuse large B cell lymphoma - Wang, Liang (J Hematol Oncol, 2020)
As a widely recognized standard regimen, R-CHOP (rituximab plus cyclophosphamide, doxorubicin, vincristine, and prednisone) is able to cure two-thirds patients with diffuse large B cell lymphoma (DLBCL), and the remaining patients suffer from refractory or relapsed disease due to resistance to R-CHOP and fare poorly. Unsatisfied outcomes for those relapsed/refractory patients prompted efforts to discover new treatment approaches for DLBCL, including chimeric antigen receptor T cells, bispecific T cell engagers, immunomodulatory drugs, immune checkpoint inhibitors, monoclonal antibodies, antibody–drug conjugates, molecular pathway inhibitors, and epigenetic-modifying drugs. Herein, up-to-date data about the most promising treatment approaches for DLBCL are recapitulated, and novel genetic classification systems are introduced to guide individualized treatment for DLBCL.